Rice breeding in India: eight decades of journey towards enhancing the genetic gain for yield, nutritional quality, and commodity value - Chakraborti, Mridul; C, Anil Kumar; Verma, Ram Lakhan; R, Abdul Fiyaz; KR, Reshmi Raj; Patra, B C; Balakrishnan, Divya; Sarkar, Sutapa; Mandal, Nimai P; Kar, Meera K; Meher, Jitendriya; Sundaram, R M; et al. (ORYZA-An International Journal of Rice, 2021)
The contribution of rice breeding for ensuring food security in India is well known. Organized rice breeding is nearly eight decades old in the country which started with the establishment of Central Rice Research Institute at Cuttack in the year 1946. Thereafter, the rice breeding programmes have undergone several transformations to meet the needs of stakeholders at both regional and national level. For all the rice ecologies of the country, high yielding varieties were developed by deployment of the required genes. Initially the objectives were met only through phenotypic selections based on breeders' own skills. With time, the rice breeders of the country adopted the advances in the fields of science and technologies especially in the areas of plant sciences. From theinitial phase of users of methodologies and materials developed elsewhere, the rice scientists of India have transformed themselves to discover useful genes from the vast germplasm resources of the country and utilize them as per the local requirements through marker assisted selection. Despite the progress made in last few decades, the genetic gain from breeding programmes is becoming stagnant over time and the increased yield in current years are now attributed more to production interventions. The rice breeders of India need to take advantage of the recent developments of speed breeding, whole genome sequences of various Oryza species, advanced phenomics and computational methods, high throughput genotyping platforms, tissue culture andgenome editing tools etc. to shift from its current approach of "breeding by chance" to "breeding by design" and to bring significant improvements in the rate of genetic gain per generation.